2022
DOI: 10.1021/acsami.2c11244
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Hydrothermal Synthesis of MoO2/MoS2 Nanocomposites as High-Performance Electrode Material for Supercapacitors

Abstract: By only changing the ratio of Mo to S source, a distinctive single phase MoO 2 or MoS 2 and MoO 2 /MoS 2 nanocomposites (NCs) are obtained through a simple one-step hydrothermal method based on CH 4 N 2 S as a sulfur source and (NH 4 ) 6 Mo 7 O 24 •4H 2 O as a source of Mo in oxalic acid. The effect of ratio of Mo to S source on the composition, structure, and electrochemical performance are systematically researched. Due to its unique design, abundant macropores active sites in MoO 2 / MoS 2 NCs induce superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…4 In the high-frequency region, the charge transfer resistance ( R ct ) can be expressed by the diameter of the semicircle, primarily reflecting the ion transfer between the electrolyte and the material. 51 The intersection with the real axis corresponds to the equivalent series resistance ( R s ), which arises from the intrinsic resistance of both the electrolyte and the electrode. 19 The R s and R ct values for pure NF, NiFe 0.5 /NF, Ni 1 (Fe/Co = 2/1) 0.5 /NF, Ni 1 (Fe/Co = 1/1) 0.5 /NF, Ni 1 (Fe/Co = 1/1) 0.5 /NF and NiCo 0.5 /NF calculated using ZsimpWin software are 0.882 Ω, 1.051 Ω, 1.002 Ω, 0.857 Ω, 0.978 Ω, and 0.915 Ω and 4.89 Ω, 4.44 Ω, 3.07 Ω, 1.69 Ω, 3.52 Ω, and 2.91 Ω, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the high-frequency region, the charge transfer resistance ( R ct ) can be expressed by the diameter of the semicircle, primarily reflecting the ion transfer between the electrolyte and the material. 51 The intersection with the real axis corresponds to the equivalent series resistance ( R s ), which arises from the intrinsic resistance of both the electrolyte and the electrode. 19 The R s and R ct values for pure NF, NiFe 0.5 /NF, Ni 1 (Fe/Co = 2/1) 0.5 /NF, Ni 1 (Fe/Co = 1/1) 0.5 /NF, Ni 1 (Fe/Co = 1/1) 0.5 /NF and NiCo 0.5 /NF calculated using ZsimpWin software are 0.882 Ω, 1.051 Ω, 1.002 Ω, 0.857 Ω, 0.978 Ω, and 0.915 Ω and 4.89 Ω, 4.44 Ω, 3.07 Ω, 1.69 Ω, 3.52 Ω, and 2.91 Ω, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Paper the charge transfer resistance (R ct ) can be expressed by the diameter of the semicircle, primarily reflecting the ion transfer between the electrolyte and the material. 51 The intersection with the real axis corresponds to the equivalent series resistance (R s ), which arises from the intrinsic resistance of both the electrolyte and the electrode. 19 The R S11, † the electrodes maintained 68.5% (Ni/NF), 56.2% (NiFe 0.5 /NF), and 74.9% (Ni 1 (Fe/ Co = 1/1) 0.5 /NF) of the initial capacitance after 5000 cycles at a current density of 10 mA cm −2 , respectively.…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…Impressively, the E D archived in our asymmetric supercapacitor device is higher than in the earlier literature on MoS 2 ‐based electrode materials. [ 36,52–60 ]…”
Section: Resultsmentioning
confidence: 99%
“…Impressively, the E D archived in our asymmetric supercapacitor device is higher than in the earlier literature on MoS 2 -based electrode materials. [36,[52][53][54][55][56][57][58][59][60] Notability, the superior electrochemical performance such as C sp , E D , and cyclic stability of fabricated MoS 2 @Cellulose//MZ carbon asymmetric device can be ascribed to the layered structure of MoS 2, and CFs contribute a sufficient amount of electrochemically active sites and shortened diffusion path for electrolyte ions and electrons, benefiting efficient Faradaic reactions.…”
Section: Mos 2 @Cellulose For Asymmetric Supercapacitor Assemblymentioning
confidence: 99%
“…It can be found that the template method is an effective method for controlling the structure of molybdenum disulfide, and the template method is simple to operate and easy to implement, and it is easy to control the synthesis process. 21 The hard template method has the following advantages over the soft template method: (1) the hard template method has considerable flexibility in the synthesis of nanomaterials. 22 (2) The experimental device is simple and the operating conditions are mild.…”
Section: Introductionmentioning
confidence: 99%